Endoplasmic Reticulum Stress Is Involved in Muscular Pathogenesis in Idiopathic Inflammatory Myopathies - Ma, Xue; Gao, Hua-Jie; Zhang, Qing; Yang, Meng-Ge; Bi, Zhua-Jin; Ji, Su-Qiong; Li, Yue; Xu, Li; Bu, Bi-Tao (Frontiers in Cell and Developmental Biology, 2022)
Objectives: Endoplasmic reticulum (ER) stress plays pivotal roles in regulation of skeletal muscle damage and dysfunction in multiple disease conditions. We postulate the activation of ER stress in idiopathic inflammatory myopathies (IIM). Methods: Thirty-seven patients with immune-mediated necrotizing myopathy (IMNM), twenty-one patients with dermatomyositis (DM), six patients with anti-synthetase syndrome (ASS), and ten controls were enrolled. The expression of ER stress-induced autophagy pathway was detected using histological sections, Western Blot, and real-time quantitative PCR. Results: ER stress-induced autophagy pathway was activated in biopsied muscle of patients with IMNM, DM, and ASS. The ER chaperone protein, glucose-regulated protein 78 (GRP78)/BiP expression in skeletal muscle correlated with autophagy, myofiber atrophy, myonecrosis, myoregeneration, and disease activity in IMNM. Conclusions: ER stress was involved in patients with IIM and correlates with disease activity in IMNM. ER stress response may be responsible for skeletal muscle damage and repair in IIM.